Teleoperación del robot Nao para la ejecución de tareas en espacios reducidos usando el dispositivo kinect v2. - Galarza Guerrero, David Sebastián (2018)
The purpose of this technical project is the teleoperation of the Nao Robot to perform tasks in small spaces by using the Kinect v2 device. Some algorithms were designed and implemented to teleoperate the Nao Robot through the Kinect v2 sensors. The Kinect v2 sensor is a video game controller device widely used and developed by Microsoft for the Xbox 360 video console, since June 2011 for PC through Windows. The Kinect v2 allows to establish communication, with the Kinect v2 sensors, between the user and the console without any physical contact. The sensor has a natural interface that recognizes the skeleton of the human body and replicates the movements in the interface, without the need of any device physically connected to the user, it also has a sensor which is able to recognize voice commands. Through the recognition of the movements of the human body in the Kinect v2 sensor, we have created the communication between the Kinect v2 sensor and the Nao Robot to replicate the user's movements. Sometime in the future, the Nao Robot may be able to perform dangerous tasks, so that people are not exposed to perform risky tasks in small spaces taking into account its capacity and limitations of the Nao Robot.